Comparison between successful team and unsuccessful team in shooting action during fifa world cup 2018 / Muhammad Afifuddin Mohd Azhar …[et al.] - Mohd Azhar, Muhammad Afifuddin; Mohamed Shapie, Mohamad Nizam; Sulaiman, Norasrudin; Mohamed, Muhammad Noor (Universiti Teknologi MARA, 2020)
Shooting action was a very crucial action in one football match as it influences the outcome. Analysing shooting action during prominent competition was very important because a new trends and tactical play always been implemented in this level of competition. Due to this, the purpose of present study was to analyse the shooting action between the successful and unsuccessful team during the group stage matches of FIFA World Cup 2018. Purposive sampling was used, 24-matches (n = 24) from group stage been selected, with 12 matches (n =12) from successful team and other 12 matches (n = 12) from unsuccessful teams. Successful teams been selected from top four teams that reach semi-final, while unsuccessful teams were from bottom four teams based on ranking during group stage of competition. Each team played three matches during group stage. Indicator selected, shooting action had been divided into two categories, which were the location of shooting action (inside penalty box and outside penalty box) and the area of shooting action (centre, right centre, left centre, right wing and left wing are). This study also analyses the total number of shooting actions produced by both groups. Data had been collected through a notational process (r = 0.97). Based on the finding (Independent sample t-test), there were significant differences between the successful team and unsuccessful team, when performing shooting action from inside penalty box (t = -2.216, p =0 .037), outside penalty box (t = -2.116, p = 0.046), and in total number of shooting action (t = -3.001, p = 0.007). The other indicators showed not significant differences (p > 0.05) for this study. The finding concluded that having more shooting actions during match could be beneficial for team in determining the outcome. This been proven when team produced more shooting actions during match, the outcome was a success one. This study also found that successful teams had an ability to create chances more than unsuccessful teams, either from inside penalty box or outside penalty box.